2014
DOI: 10.5851/kosfa.2014.34.4.464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality of Bologna Sausage Manufactured by Electron Beam or X-Ray Irradiated Ground Pork

Abstract: Ground lean pork was irradiated by an electron beam or X-rays to compare the effects of two types of radiation generated by a linear accelerator on the quality of Bologna sausage as a model meat product. Raw ground lean pork was vacuum packaged at a thickness of 1.5 cm and irradiated at doses of 2, 4, 6, 8, or 10 kGy by an electron beam (2.5 MeV) or X-rays (5 MeV). Solubility of myofibrillar proteins, bacterial counts, and thiobarbituric acid reactive substance (TBARS) values were determined for raw meat sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The results of the present study were in accordance with the findings of Niemand et al, (1981), Kim et al, (2012) and Shin et al, (2014) who reported that electron beam irradiation significantly reduced TVC in pork salamis and raw meat dose dependently. The shelf-life of pork salami observed under study after irradiation with 4.5kGy dose had shown the shelf-life of 27 days.…”
Section: Yeast and Mold Countsupporting
confidence: 93%
“…The results of the present study were in accordance with the findings of Niemand et al, (1981), Kim et al, (2012) and Shin et al, (2014) who reported that electron beam irradiation significantly reduced TVC in pork salamis and raw meat dose dependently. The shelf-life of pork salami observed under study after irradiation with 4.5kGy dose had shown the shelf-life of 27 days.…”
Section: Yeast and Mold Countsupporting
confidence: 93%
“…To determine lipid oxidation of Jokbal samples, TBARS value was measured using the method of Shin et al . (2014) with slight modification.…”
Section: Methodsmentioning
confidence: 99%
“…All instrumental texture analyses were measured at ambient temperature (20℃) using method of Shin et al . (2014) and a texture analyzer system (TA-XT2i, Stable Micro System, England) equipped with a probe (1.0 cm thickness).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food irradiation technology has been practically used as an effective preservative method to not only reduce initial microbial contamination, but also delay microorganism growth during storage in meat products ( Kim et al , 2012 ; Park et al , 2010 ; Roberts, 2014 ). According to Shin et al (2014) , irradiation dose over 4 kGy could be effective in controlling total aerobic bacteria in emulsion sausage. Thus, it would be reasonable to anticipate that irradiation technology contributes to ensure microbial safety of low-salt emulsion sausage.…”
Section: Introductionmentioning
confidence: 99%